Dynamics of Viral Infection and Evolution of SARS-CoV-2 Variants in the Calabria Area of Southern Italy - De Marco, Carmela; Veneziano, Claudia; Massacci, Alice; Pallocca, Matteo; Marascio, Nadia; Quirino, Angela; Barreca, Giorgio Settimo; Giancotti, Aida; Gallo, Luigia; Lamberti, Angelo Giuseppe; Quaresima, Barbara; Santamaria, Gianluca; et al. (Frontiers in Microbiology, 2022)
Here we report on the results of SARS-CoV-2 surveillance performed in an area of Southern Italy for 12 months (March 2021-February 2022). To this aim, we have sequenced RNA from 609 isolates. We have identified circulating VOCs by Sanger sequencing of the S gene and defined their genotypes by whole-genome NGS sequencing of 126 representative isolates. Our results indicated that B.1 and Alpha were the only circulating lineages in Calabria in March 2021; however, while Alpha remained the most common variant in April and May (90% and 73%, respectively) we observed a concomitant decrease in B.1 cases and appearance of Gamma cases (6% and 21%, respectively); C.36.3 and Delta appeared in June, (6% and 3%, respectively); Delta became dominant in July while Alpha continued to reduce (46% and 48%, respectively). In August Delta became the only circulating variant until the end of December. As of January 2022, Omicron emerged and took over Delta (72% and 28%, respectively). No patient carrying Beta, Iota, Mu, or Eta variants was identified in this survey. Among the genomes identified in this study, some were distributed all over Europe (B1_S477N, Alpha_L5F, Delta_T95, Delta_G181V, and Delta_A222V), some were distributed in the majority of Italian regions (B1_S477N, B1_Q675H, Delta_T95I, and Delta_A222V) and some were present mainly in Calabria (B1_S477N_T29I, B1_S477N_T29I_E484Q, Alpha A67S, Alpha_A701S, and Alpha_T724I). Prediction analysis of the effects of mutations on the immune response (i.e., binding to class I MHC and/or recognition of T cells) indicated that T29I in B.1 variant, A701S in Alpha variant, and T19R in Delta variant were predicted to impair binding to class I MHC whereas mutations A67S identified in Alpha, E484K identified in Gamma and E156G, delF157/R158 identified in Delta were predicted to impair recognition by T cells. In conclusion, we report on the results of SARS-CoV-2 surveillance in Regione Calabria in the period March 2021-February 2022, identified variants that were enriched mainly in Calabria, and predicted the effects of identified mutations on host immune response.